'Listen, empower us and take action now!': reflexive-collaborative exploration of support needs in bipolar disorder when 'going up' and 'going down'. (February 2014) - Billsborough, Julie; Mailey, Pater; Hicks, Alice; Sayers, Ruth; Smith, Roger; Clewett, Naomi; Griffiths, Christopher A.; Larsen, J.
Abstract Background: People with a diagnosis of bipolar disorder experience mood fluctuation from depression to mania, and their support needs may differ during these fluctuations. Aims: To investigate support needed during periods of mania and depression, and when 'going up' or 'going down'. Method: Five service user researchers were supported in a reflexive-collaborative approach to undertake and analyse semi-structured interviews with 16 people with a diagnosis of bipolar disorder and 11 people providing informal support. Results: Support needs differed when becoming manic or depressed. When manic, people needed a calming approach and encouragement to avoid overly stimulating activities. When depressed, positive activity and engaging in everyday life routines were helpful. Three core themes determined the effectiveness of support: (1) being listened to with active engagement through affirmation and encouragement, (2) empowerment through development of personal coping and self-management strategies, and (3) early action and understanding of early warning signs to respond to developing crises and protect wellbeing. Conclusion: Periods of depression or mania, and lesser 'ups' and 'downs', all require different support needs. Active listening and engagement, facilitating empowerment and appropriate early action are crucial elements of effective support.